PENGARUH BAURAN PEMASARAN DAN KINERJA KEWIRANIAGAAN TERHADAP KEPUASAN PELANGGAN PADA PT. SIMPATIK CABANG GOWA - Muhammad Amir (Jurnal Bisnis dan Kewirausahaan, 2017)
The purpose of the research were 1) to analyze the effect of mix marketing consisted of product, price, promotion, distribution line added by salesperson performance toward the increasing of sale volume at PT SImpatik Gowa, 2) to identify the influence the most dominant variable toward the increasing of sale volume at Simpatik Gowa. The research was conducted at PT Simpatik Gowa by 395 number of population. The total samples were 80. The data were collected by giving questionnaire and documentation. The research used descriptive statistic analysis and double linear regression with SPSS 20. The result of the research by simultaneously and partially showed that variable of product, price, channels distribution and performance of salesperson gave the positive influence significantly toward variable of the increase of sale volume, except the variable of promotion gave the inversely proportional influence toward the sale volume of PT Simpatik Gowa. Moreover, in partially, the variable of product was the most dominant influence to the increase of sale volume than the other variables.